Simulation of boreal summer intraseasonal oscillations in the latest CMIP5 coupled GCMs. Issue 10 (29th May 2013) - Sabeerali, C. T.; Ramu Dandi, A.; Dhakate, Ashish; Salunke, Kiran; Mahapatra, S.; Rao, Suryachandra A.
Abstract: [1] The simulation of the boreal summer intraseasonal oscillation (BSISO) has been analyzed in the historical run of the 32 models, which participated in the Coupled Model Intercomparison Project phase5 (CMIP5), and it is shown that the current state‐of‐the‐art general circulation models (GCMs) still have difficulties to properly simulate the BSISO. Compared to CMIP3 models, more CMIP5 models simulated the northward propagation of BSISO. The majority of the models could not simulate the spatial pattern of BSISO variance over the Asian summer monsoon (ASM) region and many of them failed to capture all the three peak centers of BSISO variance over the Indian summer monsoon region. Many of the models underestimated the BSISO variance over the equatorial Indian Ocean, and it is associated with the seasonal mean dry biases over this region. A reasonable representation of the intraseasonal sea surface temperature and its coupling to the convection over the equatorial Indian Ocean and an equatorial eastward propagation of convective anomalies beyond 100 ° E assure realistic simulation of BSISO over the ASM domain. We found that the models MIROC5, IPSL‐CM5A‐LR, GFDL‐CM3, CMCC‐CM, and MPI‐ESM‐LR are able to represent reasonable BSISO characteristics and can be used to unravel the modulation of BSISO characteristics due to various projected climate changes. Key Points: Current GCMs still have difficulties in simulating BSISO ISO of SST and equatorial eastward propagation of convection assure better BSISO MPI‐ESM‐LR is the best in representing the BSISOs among CMIP5 models